2018
DOI: 10.1093/bioinformatics/bty160
|View full text |Cite
|
Sign up to set email alerts
|

RapidRMSD: rapid determination of RMSDs corresponding to motions of flexible molecules

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Inspired by the quaternion arithmetic applied to the best superposition of a set of points [21,22,23] together with our recent developments [24,25], we propose a new symmetry measure and an analytical method to find the best symmetry axes of a symmetrical assembly possessing a cyclic C n symmetry. We should specifically emphasize that our method assumes that the pointto-point correspondence between the different subunits of the assembly is known.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the quaternion arithmetic applied to the best superposition of a set of points [21,22,23] together with our recent developments [24,25], we propose a new symmetry measure and an analytical method to find the best symmetry axes of a symmetrical assembly possessing a cyclic C n symmetry. We should specifically emphasize that our method assumes that the pointto-point correspondence between the different subunits of the assembly is known.…”
Section: Introductionmentioning
confidence: 99%
“…However, in general case, the complexity of the RMSD computation is linear with respect to the number of atoms in a molecule. Nonetheless, recently, we showed that in a particular case of orthogonal deformations, it is possible to compute RMSD much faster . Thus, it will be interesting to extend Carbon as the flexible refinement method using the orthogonal deformations, such as normal modes, in the further studies.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to lRMSD calculations based on matrix decompositions-such as SVD, a fast determination of the optimal rotation matrix based on a Newton-Raphson quaternion-based method was reported [4]. Finally, recent work addressed the calculation of RMSD between flexible structures, the flexibility being modeled using collective coordinates obtained via normal mode analysis or PCA [15]. This latter work is especially interesting as it targets deformable structures modeled by means of collective motions.…”
Section: Rmsd Lrmsd and Their Variantsmentioning
confidence: 99%